2019
DOI: 10.1111/ajr.12568
|View full text |Cite
|
Sign up to set email alerts
|

Acute post‐streptococcal glomerulonephritis in Central Australia

Abstract: Objective To determine the incidence, clinical presentation and progress of acute post‐streptococcal glomerulonephritis in Central Australia. Design Retrospective observational analysis. Setting Paediatric inpatient admission at Alice Springs Hospital. Participants Patients admitted to Alice Springs Hospital under 14 years of age meeting diagnostic criteria for acute post‐streptococcal glomerulonephritis between January 2010 and December 2014. Main Outcome Measures Incidence of acute post‐streptococcal glomeru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 17 publications
0
9
0
3
Order By: Relevance
“…Similarly, a 2010-2014 study from Central Australia found that all children hospitalised with APSGN were Aboriginal and Torres Strait Islander. 24 The disparities in kidney disease burden for Aboriginal and Torres Strait Islander children in Australia is akin to other First Nations' experience around the world. For example, a study from New Zealand reported that the incidence of APSGN was 7-to 17-fold higher amongst Pacific Islander and M aori children compared to those of European descent.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a 2010-2014 study from Central Australia found that all children hospitalised with APSGN were Aboriginal and Torres Strait Islander. 24 The disparities in kidney disease burden for Aboriginal and Torres Strait Islander children in Australia is akin to other First Nations' experience around the world. For example, a study from New Zealand reported that the incidence of APSGN was 7-to 17-fold higher amongst Pacific Islander and M aori children compared to those of European descent.…”
Section: Discussionmentioning
confidence: 99%
“…infection. Delayed access to specialized burn centers located in major Australian cities, due to distance and transport availability, may contribute to 69,72 This health inequity may be minimized in these cases through careful education, ongoing monitoring, and early treatment of Aboriginal and Torres Strait Islander burn injury survivors and their family, to help prevent further manifestation of Streptococcus sp. or significant comorbidities later in life.…”
Section: Discussionmentioning
confidence: 99%
“…Aboriginal children in Australia have the highest incidence of post-infectious glomerulonephritis (PIGN) in the world; recent studies from Central Australia reported an incidence of 229/100,000 person years [8]. Furthermore, rates in parts of Australia continue to be elevated despite reduction in PIGN rates in many other parts of the world [9].…”
Section: Australia-aboriginal and Torres Strait Islandersmentioning
confidence: 99%